THE INFLUENCE OF HEALTH WORKER PRODUCTIVITY ON IMPROVING HEALTH SERVICES AT SETIABUDI PUBLIC HEALTH CENTER, SOUTH JAKARTA - Raden Partinah; Teguh Nurhadi Suharsono; Raden Ricky Agusiady T S; Ayu Laili Rahmiyati; Didin Saepudin; Farida Yuliaty (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of health worker productivity on improving health services at the Setiabudi Community Health Center in South Jakarta. The research method used is descriptive quantitative with a sample of 90 respondents. Primary data were collected through questionnaires and processed using the Method of Successive Interval (MSI) to convert ordinal scale data into interval scales before conducting prerequisite tests and hypothesis testing. Data analysis used multiple linear regression. The results of the F test showed that the variables of motivation, income level, work environment, opportunity for achievement, management, and nutritional status simultaneously had a significant effect on health services (F count 12.053; Sig < 0.001) with a contribution (R^2) of 46.6%. Partially, the management variable was the most dominant factor influencing service improvement (t count 5.608; Sig < 0.001). The implications of this study emphasize the importance of strengthening the managerial system and work motivation to optimize the quality of public health services